The Cambridge companion to the Scottish enlightenment - Broadie, Alexander; Smith, Craig (Cambridge University Press, New York, 2019)
The second edition of this Companion presents a philosophical perspective on an eighteenth-century phenomenon that has had a profound influence on Western culture. This volume contains five entirely new chapters on morality, the human mind, aesthetics, sentimentalism and political economy, and eleven other chapters have been significantly revised and updated.
Includes bibliographical references (p. 348-356) and index.
Keywords: Philosophy, Scottish -18th century; Enlightenment -Scotland.; Scotland - Intelectual life - 18th century; Intellectual life